Penggunaan Biosurfaktan Lerak (Sapodium Rarak), Aditif Lidah Buaya dengan Essential Oil Kopi dan Melati pada Sabun Cuci Tangan - Evi Uswatun Khasanah; Tsabita Kamilatul Mustabsyiroh; Adi Helmi; Anisa Khoiriyah; Khusna Widhyahrini; Wahidin Wahidin (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
This study aims to develop a natural hand soap as an alternative to conventional soaps that commonly contain synthetic surfactants such as Sodium Lauryl Sulfate (SLS), which may cause skin irritation and environmental pollution. The product was developed using natural biosurfactants derived from lerak fruit (Sapindus rarak), aloe vera gel, and coffee and jasmine essential oils as natural fragrances. The research employed a Research and Development (RD) method using the 4D development model, consisting of Define, Design, Development, and Dissemination stages. The production process included the extraction of lerak saponins, preparation of aloe vera gel, formulation of the liquid soap mixture, and the addition of essential oils to improve aroma and sensory quality. Product evaluation was conducted through expert validation, user response questionnaires, and product stability observations, which were analyzed using descriptive quantitative and qualitative methods. The results showed that lerak saponins were effective as natural biosurfactants with cleansing and antibacterial properties, while aloe vera functioned as a moisturizer that helped reduce skin dryness. The addition of coffee and jasmine essential oils enhanced the fragrance and provided a mild relaxing effect. The resulting product was considered safe, environmentally friendly, economical, and suitable for use as a project-based science learning medium to support clean and healthy living behavior (PHBS) and entrepreneurship development in schools.